VaR and CVaR implied in option prices - Giovanni Barone Adesi (Journal of Risk and Financial Management, 2016)
VaR (Value at Risk) and CVaR (Conditional Value at Risk) are implied by option prices. Their relationships to option prices are derived initially under the pricing measure. It does not require assumptions about the distribution of portfolio returns. The effects of changes of measure are modest at the short horizons typically used in applications. The computation of CVaR from option price is very convenient, because this measure is not elicitable, making direct comparisons of statistical inferences from market data problematic.
Keywords: 330; VaR; expected shortfall; put option